Pengembangan Game Edukasi Matematika Berbasis Aplikasi Android untuk Meningkatkan Kemampuan Literasi Numerasi Siswa SMP - Hendrisa Adrillian; Nizaruddin Nizaruddin; Aurora Nur Aini (Jurnal Kualita Pendidikan, 2023)
Interactive learning media can be used as a learning tool to improve the numeracy literacy skills of junior high school students, one of which is educational games. Educational games are games that contain educational content and are used to make it easier for students to understand the material provided. Development research using the ADDIE model was used to develop numeracy literacy educational games for junior high school students on statistics material. The population of this study were students of class VIII SMP Kesatrian 1 Semarang. The sample of this research is class VIII A, VIII C, and VIII D. The research design is Posttest Only Control Design. The data collection used is the observation method, the test method, the documentation method. The results of this study indicate that math educational games to improve numeracy literacy skills in statistical material are valid and practical to use based on validation assessments by media experts, material experts, and student response questionnaires. Furthermore, the developed educational game is effectively used in learning mathematics to improve the numeracy literacy skills of junior high school students based on the right-tail side t test, the percentage of student activity, the teacher's ability to manage learning, and student completeness in learning. Android-based math educational games are said to be valid, practical, and effective for improving junior high school students' mathematical numeracy literacy skills in statistics material.